Promoting Latinx health equity through community-engaged policy and practice reforms in North Carolina - Thoumi, Andrea; Plasencia, Gabriela; Madanay, Farrah; Ho, Ethan Shih-An; Palmer, Caroline; Kaalund, Kamaria; Chaudhry, Nikhil; Labrador, Amy; Rigsby, Kristen; Onunkwo, Adaobi; Almonte, Ivan; Gonzalez-Guarda, Rosa; et al. (Frontiers in Public Health, 2023)
Introduction The Latinx Advocacy Team & Interdisciplinary Network for COVID-19 (LATIN-19) is a unique multi-sector coalition formed early in the COVID-19 pandemic to address the multi-level health inequities faced by Latinx communities in North Carolina. Methods We utilized the National Institute on Minority Health and Health Disparities (NIMHD) Research Framework to conduct a directed content analysis of 58 LATIN-19 meeting minutes from April 2020 through October 2021. Application of the NIMHD Research Framework facilitated a comprehensive assessment of complex and multidimensional barriers and interventions contributing to Latinx health while centering on community voices and perspectives. Results Community interventions focused on reducing language barriers and increasing community-level access to social supports while policy interventions focused on increasing services to slow the spread of COVID-19. Discussion Our study adds to the literature by identifying community-based strategies to ensure the power of communities is accounted for in policy reforms that affect Latinx health outcomes across the U.S. Multisector coalitions, such as LATIN-19, can enable the improved understanding of underlying barriers and embed community priorities into policy solutions to address health inequities.